Scale Effect on the Behavior of Geotextile-Reinforced Soil Under Square Footing - Khowla Imbark; Enas Altalhe (AlQalam Journal of Medical and Applied Sciences, 2025)
The present research investigates how footing width affects the geotextile-reinforced clay soil’s bearing capability. A numerical simulation of footing width was used to examine how bearing ca-pacity changes with width, and several laboratory experiments were conducted to investigate how footing width affects the behavior of reinforced soil. The results display that as footing width in-creases, so does the load bearing capacity; this effect was most pronounced between 80 and 250 mm, after which there was little difference in the bearing capacity settlement curves. Depending on the reinforcement ratio Rr, the impact of the bearing capacity ratio in reinforced soil may vary as the footing width changes. The BCR barely changed when the footing width was changed at Rr of 4. The models with larger footing widths had a higher BCR than those with smaller footing widths at reinforcement ratios below 4. BCR values for smaller model scales were higher for reinforcement ratios larger than 4. يهدف هذا البحث في التحقق من تأثير عرض الأساس على قدرة تحمل التربة الطينية المسلحة بالجيوتكستايل. استُخدمت محاكاة عددية لعرض الأساس لدراسة كيفية تغير قدرة التحمل مع العرض، وأُجريت العديد من التجارب المعملية لدراسة كيفية تأثير عرض الأساس على سلوك التربة المسلحة. تُظهر النتائج أنه مع زيادة عرض الأساس، تزداد قدرة التحمل؛ وكان هذا التأثير أكثر وضوحًا لعرض أساس بين 80 و250 مم، وبعد ذلك كان هناك فرق ضئيل في منحنيات قدرة التحمل - الهبوط. اعتمادًا على نسبة التسليح Rr، قد يختلف تأثير نسبة قدرة التحمل في التربة المسلحة مع تغير عرض الأساس. بالكاد تغير BCR عند تغيير عرض الأساس عند Rr تساوي 4. كان للنماذج ذات عرض الأساس الأكبر BCR أعلى من تلك ذات عرض الأساس الأصغر عند نسب تسليح أقل من 4. كانت قيم BCR لمقاييس النماذج الأصغر أعلى لنسب التسليح الأكبر من 4.